Procedure of concluding ‘concordat’ marriage – administrative or civil? - Tunia, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The procedure of concluding ‘concordat’ marriage covers a complex of specific actions whose fulfilment is necessary for an effective occurrence of marriage in the area of the Polish law and the Catholic Church law. In its course one can distinguish a few comprising stages, i.e. actions preceding conclusion of marriage, actions associated with concluding marriage and actions connected with registration of marriage. The subject at issue contains both administrative law and civil law elements. The goal of the article is to determine which elements from the procedure of concluding ‘concordat’ marriage have the administrative character and which of them fall within the scope of the civil law interest. Moreover, attention has been paid to a mode of regulating rules which standardize the procedure of concluding ‘concordat’ marriage in the context of reception of legal and canonical norms in the area of the mentioned fields of the Polish law.